C1 Pharyngeal lymphogranuloma venereum: four cases in men who have sex with men. (23rd May 2012) - Dosekun, O; Edmonds, S; Stockwell, S; French, P; White, J A
Abstract : Background: Lymphogranuloma venereum (LGV) is an established cause of proctitis in men who have sex with men (MSM). In the UK, testing for pharyngeal Chlamydia trachomatis (CT) is not routine, and LGV typing is seldom performed. Objective: To describe clinical features of four cases of pharyngeal LGV seen across three different urban GUM/HIV clinics, all of who had LGV-specific DNA detected at this site. Case reports: All four cases occurred in MSM; their past STI histories included HIV (2), syphilis (3) and hepatitis C (2; one diagnosed after LGV infection). Two cases had no oropharyngeal symptoms or local lymphadenopathy (LN) but had symptomatic LGV proctitis. One case had severe odynophagia, a tongue ulcer and cervical LN, and the final case reported severe pharyngitis with large unilateral cervical LN 10 days prior. Three of the four had concurrent rectal LGV infection. The infections responded to doxycycline: 21 days was given in two cases, and the other two received 7 and 14 days treatment, respectively. Test of cure swabs performed at 6 weeks to 5 months following treatment were negative in all cases. Three MSM had new STIs diagnosed at the time of their Test of cure. Conclusion/Learning points: We describe a variety of clinical presentations of pharyngeal LGV infection in MSM. The oropharynx may act as reservoir for CT, and possibly LGV, and routine screening should be considered at this site for all MSM. The absence of localised symptoms does not exclude pharyngeal LGV infection. Symptomatic oropharyngeal LGV infection is probably rare but should be considered in the differential diagnosis of MSM with unusual or severe symptoms/signs at this site. There are no guidelines for treating pharyngeal CT or LGV infection, but treatment with 1- to 3-week regimens of doxycycline was effective. Ongoing high-risk sexual behaviour in this population makes outbreak containment difficult.